(untitled) (Journal of the College of Basic Education, 2023)
The research aims to conduct an evaluation of the work of the Iraqi Scientific Virtual Library afterIt was established more than ten years ago, which is a sufficient period to demonstrate its work and the extent of its usefulness to researchers inUniversity of Technology from naming the library, which has become inappropriate for its contents; and pointing out the defectAfter transferring the responsibility for managing the system from the American side to the Iraqi side, there are ways to show itinformation by them in a way that makes it difficult for the beneficiary to directly access that informationand the large number of publishers unconsidered; The research also touched on the strict instructions fromThose responsible for the virtual library accepted the obligation to subscribe to the library 6 and to set non-conditionsIt is legal for those who did not participate in that library, such as stopping the promotion of a teacher. The research has foundTo many recommendations, including deleting the names or data of every participant who is not affiliated with the universitytechnological. Selection of books, periodicals and databases according to the actual needs of its membersTechnology University. Cancellation of the conditions added to the promotion of teaching staff that require subscription to the librarydefault. In addition to changing the name of the Iraqi Virtual Scientific Library to a nameIraqi Virtual Library.Keywords: Iraqi Virtual Library / University of TechnologyIntroduction Developments in information and communication technology in the 1980sThe nineties greatly affected the applications of information systems in public and private institutions ©After the advent of local and remote networks, distributed computing, systems and networks of the Internet